Kritik Terhadap Bentuk Kuantifikasi Nilai Kebaikan pada Ajaran Kebaikan dalam Islam - Rilliandi Arindra Putawa (Undiksha, 2022)
The existence of numbers as symbols that are universal is often used to help humans understand a phenomenon. Numbers can make something easier to determine benchmarks in various ways, including values that were previously qualitative. Qualitative value quantification have been known in Islamic values, one of which is in explaining the quality of a worship or goodness done by mankind. This study aims to explore the phenomenon of value quantification in the Qur'an and analyze it from a philosophical point of view, especially in the field of ethics. This research is a research on the actual problem, where the quantification of qualitative value is considered as a phenomenon that has philosophical value in it. The data that has been collected is then grouped into parts, which are then searched for correlations, so that philosophical knowledge can be obtained regarding the quantification of values in the Qur’an. The results of the study indicate that the concept of sincerity in the Qur’an makes the calculation of the value of goodness cannot becarried out completely quantitatively by humans. The concept of sincerity seems to re-abstractthe results of the quantification of values contained in ethical statements in the Al-Quran and Hadith.